2018
DOI: 10.5194/os-2018-53
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Frictional interactions between tidal constituents in tide-dominated estuaries

Abstract: Abstract. When different tidal constituents propagate along an estuary, they interact because of the presence of nonlinear terms in the hydrodynamic equations. In particular, due to the quadratic velocity in the friction term, the effective friction experienced by both the predominant and the minor tidal constituents is enhanced. We explore the underlying mechanism with a simple conceptual model by utilizing Chebyshev polynomials, enabling the effect of the velocities of the tidal con-5 stituents to be summed … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…We developed an analytical approach to link average water depths to tidal regime shifts to understand how morphological alteration affects tidal hydrodynamics in estuaries. The hydrodynamic model proposed by Cai et al (2018) was used to explore hydrodynamic changes in Lingdingyang Bay, where we observed an apparent hydrodynamics regime shift as a result of channel deepening and narrowing caused by human‐induced interventions (e.g., channel dredging, sand excavation, and land reclamation).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…We developed an analytical approach to link average water depths to tidal regime shifts to understand how morphological alteration affects tidal hydrodynamics in estuaries. The hydrodynamic model proposed by Cai et al (2018) was used to explore hydrodynamic changes in Lingdingyang Bay, where we observed an apparent hydrodynamics regime shift as a result of channel deepening and narrowing caused by human‐induced interventions (e.g., channel dredging, sand excavation, and land reclamation).…”
Section: Discussionmentioning
confidence: 93%
“…To predict the responses of hydraulic processes to future changes, it is necessary to understand the impacts of human interventions on the tidal regimes of estuaries. As the analytical approach has also been successfully applied in Guadiana Estuary (Cai et al, 2018), our approach for quantifying the impacts of morphological alterations on tidal hydrodynamics in Lingdingyang Bay could be applied more broadly for tide‐dominated estuaries worldwide, where human interventions (i.e., channel deepening) are taking place.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations